Vaccine To Confer to Nonhuman Primates Complete Protection against Multistrain Ebola and Marburg Virus Infections - Swenson, Dana L. (American Society for Microbiology (ASM), 2008)
Filoviruses (Ebola and Marburg viruses) are among the deadliest viruses known to mankind, with mortality rates nearing 90%. These pathogens are highly infectious through contact with infected body fluids and can be easily aerosolized. Additionally, there are currently no licensed vaccines available to prevent filovirus outbreaks. Their high mortality rates and infectious capabilities when aerosolized and the lack of licensed vaccines available to prevent such infectious make Ebola and Marburg viruses serious bioterrorism threats, placing them both on the category A list of bioterrorism agents. Here we describe a panfilovirus vaccine based on a complex adenovirus (CAdVax) technology that expresses multiple antigens from five different filoviruses de novo. Vaccination of nonhuman primates demonstrated 100% protection against infection by two species of Ebola virus and three Marburg virus subtypes, each administered at 1,000 times the lethal dose. This study indicates the feasibility of vaccination against all current filovirus threats in the event of natural hemorrhagic fever outbreak or biological attack.